MEGADIVERSE COUNTRIES: AN INTEGRATIVE MULTIVARIATE ANALYSIS OF SPECIES RICHNESS, ITS DRIVERS, AND CONSERVATION CHALLENGES IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT GOAL 15 – LIFE ON LAND - Yánez-Moretta, Patricio (Editora Impacto Científico, 2025)
Megadiverse countries harbor the majority of the world’s biological diversity and play a pivotal role in achieving global biodiversity conservation goals. This study presents a comprehensive multivariate analysis of species richness across vascular plants and vertebrate groups in twenty megadiverse countries, examining the ecological, geographical, climatic, and evolutionary drivers underlying their exceptional biodiversity. Using comparative data on species richness, land area, and multivariate ordination techniques, we identify patterns linking tropical and subtropical climates, habitat heterogeneity, historical biogeography, and isolation processes to high levels of biodiversity and endemism. The results highlight that species richness is not strictly proportional to country size, as smaller tropical nations such as Ecuador and Malaysia exhibit disproportionately high biodiversity densities. In addition to identifying biodiversity patterns, this study discusses the major conservation challenges faced by megadiverse countries, including deforestation, habitat fragmentation, climate change, and unsustainable resource use. Framed within the context of Sustainable Development Goal 15 (Life on Land), the findings emphasize the critical importance of megadiverse countries for global biodiversity conservation and the urgent need for integrated, socially inclusive, and sustainable conservation strategies aligned with the objectives of the 2030 Agenda.DOI: https://doi.org/10.56238/edimpacto2025.088-003